Pessoas negociando pessoas: o mercado de escravos de Bonfim do Paraopeba (MG) e suas conexões (1842-1888) - Ulisses Henrique Tizoco (2018)
This research aims to analyze the characteristics of the domestic slave trade in Bonfim do Paraopeba (MG), as well as to identify the connections established with markets of other regions of the Brazilian Empire between 1842 and 1888, especially during the final three decades of slavery, when the domestic trade (in its intra and interprovincial modalities) played an important role in the replacement of captive labor in Brazil. The research is largely based on data retrieved from records of commercial transactions involving human merchandise found in notarial records and proxies housed in the Bonfim Municipal Public Archive, as well as other notary and printed sources from the period in focus. I hope to show that, after the cessation of the Atlantic Slave Trade in 1850, the internal movements of captives taking place in southeastern Brazil, and in the province of Minas Gerais in particular, were part of much larger and more complex processes that went beyond a simple transfer of slaves hypothetically unnecessary from supposedly decadent areas to economically more dynamic regions.